The Effect of the Use of Position Clocks on the Risk of Pressure Wounds in Patients at HCU Bali Mandara Hospital - Tresna Dewi, Ni Luh Ayu Sulistiani; Ayu Martini, Ni Made Dwi; Swastikaningtyas, Niluh Nyoman Tantri; Pradnya Susila, I Made Dwie (STIKES Hesti Wira Sriwijaya, 2026)
Introduction: Pressure ulcers are localized injuries to the skin and/or underlying tissue, primarily caused by prolonged pressure, especially among patients with limited mobility. These ulcers can lead to pain, infection, extended hospital stays, and increased healthcare costs. Pressure ulcer prevention is a critical component of nursing care. One effective non-pharmacological intervention is the use of a clock position, a visual aid designed to remind nurses or caregivers to reposition patients regularly, ideally every two hours. This study aimed to determine the effect on the usage of clock position towards the risk of developing pressure ulcers in bedridden patients at the High Care Unit (HCU) of RSUD Bali Mandara. Method: The study utilized a pre-experimental design with a one-group pre-test and post-test approach. A total of 32 respondents were selected using purposive sampling. The Braden Scale was utilized to assess the risk of pressure ulcers. The intervention was conducted in three days using the clock position method, which involved rotating patients’ positions every two hours (supine, right lateral, left lateral) with a 30° head elevation. Data was analyzed using the Wilcoxon Signed Ranks Test. Results: The result showed that most respondents were initially at high to severe risk of pressure ulcers, but after the intervention, the majority shifted to moderate and low-risk categories. Statistical analysis showed a p-value of 0.001 (p < 0.05), indicating a significant effect of the clock position intervention in reducing the risk of pressure ulcer. Conclusion: In conclusion, a systematic intervention of clock position is effective in lowering the risk of pressure ulcers in bedridden patients. This intervention can be integrated as part of standard nursing care in intensive care settings.